Does bank size matter for Islamic banks' profitability? The insight from Indonesia - Yaseen, Atif; Widarjono, Agus (Proceeding International Conference on Accounting and Finance, 2024)
This research explores how bank size affects the profitability of Islamic banks in Indonesia, a predominantly Muslim country. The goal of this study is to answer an ongoing debate about whether Islamic banks should be large or small. We employ 31 banks and use quarterly data from 2014 to 2020 with unbalanced panel data. We document that the impact of bank size on profitability is non-linear in terms of the U-shaped impact. Raising bank size first worsens the profitability, but once it achieves a threshold value, it boosts profitability. Therefore, our findings confirm the advantages of having larger Islamic banks instead of small Islamic banks.